New taxonomic, stratigraphic, and geographic information on the genus Faksephyllia Floris, 1972 (Scleractinia; Caryophylliidae); first records from the Oligocene of Austria, Germany, and Italy - Baron-Szabo, Rosemarie C. (Zootaxa, 2016)
The scleractinian genus Faksephyllia Floris, 1972, is revised based on the study of original and topotypic material as well as original descriptions. Representatives of this genus have been reported from only a small number of lower Paleogene localities, including the Danian of Azerbaijan, Denmark (Greenland), Kazakhstan, and Sweden, as well as the Paleocene of Austria and Denmark (Fakse). New material belonging to the type species of Faksephyllia (F. faxoensis) is described from the Lower Oligocene of Austria (Northern Calcareous Alps, Tyrol). In addition, material from the Oligocene of Germany and the Lower Oligocene of Italy, formerly grouped with the genera Calamophyllia and Rhabdophyllia, are here re-assigned and transferred to Faksephyllia. The genus Faksephyllia remains a monospecific taxon, including only the type species, Faksephyllia faxoensis (Beck, in Lyell). In addition, Faksephyllia represents the earliest colonial genus among the caryophylliids.